COVID-19 RELATED NEOLOGISMS IN ENGLISH AND UZBEK: SEMANTIC, MORPHOLOGICAL, AND PRAGMATIC ANALYSIS (EduVision: Journal of Innovations in Pedagogy and Educational Advancements, 2025)
The COVID-19 pandemic has had a profound impact on all aspects of human life, including language. This study examines neologisms that emerged in English and Uzbek during the pandemic, analyzing their semantic, morphological, and pragmatic features. Data were collected from media texts, social networks, and official documents between 2020 and 2022. Findings reveal that neologisms enriched medical terminology, influenced social life, education, work processes, and communication, and demonstrated language integration and adaptation. The most productive areas for neologism formation were social life and education. The study also highlights cultural and contextual adaptations in both languages.